Impacto ambiental do esgoto hospitalar no vale do submédio São Francisco - Peres, Wolmir Ercides (2013)
This study aims to map the environmental impact in the valley lower basin of the São Francisco river, caused by liquid waste from the sewage and wastewater from two hospitals located in the cities of Juazeiro / BA and Petrolina / PE, identifying the composition of the waste and its potential risk to health and environment and can affect local population and quality of water supplied population and irrigation. This research aims General: to map the environmental impact of waste liquids from sewage and wastewater from health facility in the sub-medium São Francisco Valley, through the analysis of effluents produced by public hospitals in the municipalities of Petrolina / PE and Juazeiro / BA. In order to enable the achievement of the ultimate goal was traced to some specific objectives are: to identify the main points of discharge of effluents and their potential for contamination; to determine the physico chemical and biological effluents and wastewater hospitals in these health services; to evaluate the water quality at the point of hospital discharge of effluents; to evaluate the environmental impact of waste, its pathogenicity and risks to community health. It will be collecting samples of waste water and five points, two on the river (P1: capitation and P5: discard), and three others located at the headquarters of municipalities (P2: supply network location; P3: hospital level and P4: treatment station). After a comparative analysis will be made to the parameters established with current legislation, and culminated in drafting proposals to compose the local waste management of health services-PGRSS. So opted for a procedure comparative methodological character, alternating with reflections moments order space-socialenvironmental in order to base the research giving you tools to formulations thoughts, using several authors that, in principle, are in different areas of science, but whose thoughts when articulated produce knowledge necessary to understand the question posed in an effort multi-and transdisciplinary. At the end of this research showed that respondents were sensitive indicators, with regard to the environmental impacts of this effluent, and showing that there is a difference between the hospital and domestic sewage and that they should receive different treatments before being returned to the body water.